2005
DOI: 10.1111/j.1348-0421.2005.tb03673.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Virulent Mycobacterium tuberculosis Involves Preventing Apoptosis Induced by Bcl‐2 Upregulation and Release Resulting from Necrosis in J774 Macrophages

Abstract: Macrophage apoptosis plays a role in mycobacterial infection. To define the mechanism by which virulent Mycobacterium tuberculosis escapes apoptosis and killing in macrophages, J774 macrophages were infected with virulent M. tuberculosis H37Rv and attenuated H37Ra strains. H37Rv induced less apoptosis than H37Ra, and caspase 3 was activated in H37Ra‐ and H37Rv‐infected macrophages. Intracellular H37Rv bacilli were released at a higher rate into the supernatant than were H37Ra by the sixth day of infection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 27 publications
6
60
0
Order By: Relevance
“…This hypothesis is compatible with the in vitro data already published showing inhibition of apoptosis in infected macrophages by virulent M. tuberculosis (but not avirulent mycobacteria) [27,28,55,[59][60][61][62][63]. It is also consistent with multiple reports suggesting that upregulation of Fas/FasL in vivo is specifically associated with T-cell death in TB [38,[64][65][66][67].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This hypothesis is compatible with the in vitro data already published showing inhibition of apoptosis in infected macrophages by virulent M. tuberculosis (but not avirulent mycobacteria) [27,28,55,[59][60][61][62][63]. It is also consistent with multiple reports suggesting that upregulation of Fas/FasL in vivo is specifically associated with T-cell death in TB [38,[64][65][66][67].…”
Section: Discussionsupporting
confidence: 81%
“…Fortunately, there are two findings that may explain the apparent paradox. It has been suggested that M. tuberculosis can subvert the apoptotic cascade by modulating expression of markers downstream of primary signaling [54,55]. We therefore analyzed expression of a number of apoptosismodulating genes downstream of these markers and in selected cases, also at expression of these genes in CD14…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it has been well discussed that infection with virulent M. tuberculosis induces necrosis rather than apoptosis (4-7). Zhang et al (6) reported that a virulent M. tuberculosis strain has the ability to upregulate Bcl-2 expression, which could attenuate the proapoptotic function of Bim. To establish a new clinical anti-M. tuberculosis treatment based on our findings, further examinations are needed that clarify the role of the proapoptotic response observed in this study during virulent M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of apoptosis and its manipulation by M.tb becomes increasingly evident [80,81]. Moreover, H37Rv, but not H37Ra, inhibits apoptosis in vitro [82] and causes exacerbated necrosis in Mf in vitro [83]. Apoptosis sensitizer gene BTG1, synergistically enhanced by LPS and IFN-g, has been implicated in activation-induced apoptosis [84].…”
Section: Immunosuppressionmentioning
confidence: 99%